If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying d + 4 = 23 Reorder the terms: 4 + d = 23 Solving 4 + d = 23 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + d = 23 + -4 Combine like terms: 4 + -4 = 0 0 + d = 23 + -4 d = 23 + -4 Combine like terms: 23 + -4 = 19 d = 19 Simplifying d = 19
| 3(2x+1)=-42+15x | | y+19=40 | | 3x^2-7-74= | | -1/4(d+1)=2 | | -3x-5=2x+11 | | (x^2-x)=0 | | 21q=-735 | | (X^3x^2)+(-2x^2-9)=0 | | -5(5x+8)+7(7x-6)=62 | | 2x+10-50=50 | | x-4.1=-5 | | 3+6x=-6x+87 | | 10x-9=3x+19 | | 64-h=12 | | 3-9=9a+12 | | 9y+4=8y-1 | | 2x+9=4-3x | | 34=-(m+3) | | 4n-6-2n=-13 | | 4n+9=n-6 | | x+8=-25+4x | | x+.81=-6.3 | | 3-(y-4)=2+3(y+1) | | 2(-8-11x)=-7x+11(-11-2x) | | x-5/10=2x-3/5 | | 4x+27=3x+24 | | x+(x+28)+90=180 | | 5x^3+x^2-2x+4=0 | | -2(x+3)=7x-24 | | x+(x-25)+(x-25*3)=275 | | -6(2+a)=-48 | | 7.9=x+12.7 |